Engagements with hybridity in literature : an introduction - Kuortti, Joel; Nyman, Jopi, 1966-; Ghasemi, Mehdi (Professor of English) (New York, NY : Routledge, 2023)
"Engagements with Hybridity in Literature: An Introduction is a textbook especially for undergraduate and graduate students of literature. It discusses the different dimensions of the notion of hybridity in theory and practice, introducing the use and relevance of the concept in literary studies. As a structured and up-to-date source for both instructors and learners, it provides a fascinating selection of materials and approaches. The book examines the concept of hybridity, offers a historical overview of the term and its critique, and draws upon the key ideas, tends, and voices in the field. The book critically engages with the theoretical intellectual and literary discussions of the concept from the time of the colonialism to the postmodern era and beyond. The book enables students to develop critical thinking through engaging them in case studies addressing a diverse selection of literary texts from various genres and cultures that open up new perspectives and opportunities for analysis. Each chapter offers a specific theoretical background and close readings of hybridity in literary texts. To improve the students' analytical skills and knowledge of hybridity, each chapter includes relevant tasks, questions, and additional reference materials"--
Keywords: Cultural fusion in literature; LITERARY CRITICISM / General